A Comprehensive Review of Compartment Syndrome - Beig Mirza, Saqeb; Elawady, Khaled (IntechOpen, 2021)
Compartment syndrome is a condition caused by an increase in pressure in a closed anatomical space. It can lead to irreversible damage and necrosis of the contents of that space with devastating consequences for the patient. It can affect the musculoskeletal system as well as sites outside the musculoskeletal system including the thorax and abdomen. This book describes the occurrence of compartment syndrome at all these sites, diagnosis and adjuncts to diagnosis, and the importance of timely management of this condition to prevent major morbidity and preserve function.